The analysis of low-dose glucocorticoid maintenance therapy in patients with primary nephrotic syndrome suffering from COVID-19 - Li, Yong-Qi; Wu, Min; Wang, Yu-Jia; Zhang, Yu-Xia; Lu, Jing; Zhao, Yi-Nan; Ji, Bo-Fan; Chen, Zhi-Qing; Tang, Ri-Ning; Liu, Bi-Cheng (Frontiers in Molecular Biosciences, 2024)
Objectives: This study aimed to describe the effects of low-dose (prednisolone acetate 2.5-7.5mg/day) glucocorticoids (GCs) maintenance therapy in patients with primary nephrotic syndrome (NS) suffering from coronavirus disease 2019 (COVID-19).Methods: A single-center retrospective study of NS patients with COVID-19 infection in Zhongda Hospital Affiliated to Southeast University from February 1, 2022 to March 31, 2023 was conducted. All enrolled patients underwent renal biopsy for the pathological diagnosis and reached complete remission (CR) or near-CR before COVID-19 infection. According to the maintained therapy regimen, patients were divided into low-dose GCs group and non-GCs group.Results: A total of 125 patients were enrolled in the study. Their median age was 46.0±15.6 years, and the median value of 24-h urine protein was 0.77 g. The majority of these patients received treatment for more than six months, with a significant portion achieving CR (29.6%) or near-CR (43.2%). The leading cause of NS was membranous nephropathy (52%). There were no significant differences in the baseline characteristics between low-dose GCs and non-GCs group. As compared to those in the non-GCs group, patients receiving low-dose GCs treatment showed less fatigue or muscle weakness, smell disorder, palpitations, decreased appetite, taste disorder, dizziness, sore throat or difficult to swallow and fever (P< 0.05). Moreover, patients in the low-dose GCs group were with higher median quality of life scores (85.0) than in the non-GCs group (P=0.001). Further serum inflammatory factor analysis indicated that interleukin-6 (IL-6) levels in the non-GCs group were significantly higher than that in the low-dose GCs group (P < 0.05).Conclusions: Patients with NS in low-dose GCs maintenance therapy stage showed milder symptom, higher quality of life and decreased serum IL-6 levels compared to those, who were not on GCs This is a provisional file, not the final typeset article maintenance therapy. These results suggest the beneficial effect of low-dose GCs therapy in NS patients with CR/ near-CR suffering from COVID-19 infection.